Hemodynamic Effects of a Multidisciplinary Geriatric Rehabilitation Program - Pagonas N (Dove Medical Press, 2020)
Nikolaos Pagonas,1,2,* Frederic Bauer,1,* Laura Zappe,1 Felix S Seibert,1 Benjamin Rohn,1 Christiane Klimek,3 Rainer Wirth,3 Michael Gotzmann,4 Nina Babel,1 Timm H Westhoff1 1University Hospital Marien Hospital Herne, Department of Internal Medicine I, Ruhr-University Bochum, Bochum, Germany; 2University Hospital Brandenburg, Department of Cardiology, Brandenburg Medical School, Brandenburg an der Havel, Germany; 3University Hospital Marien Hospital Herne, Department of Geriatrics, Ruhr-University Bochum, Bochum, Germany; 4University Hospital St Josef Hospital Bochum, Cardiology, Ruhr University Bochum, Bochum, Germany*These authors contributed equally to this workCorrespondence: Timm H WesthoffUniversity Hospital Marien Hospital Herne, Department of Internal Medicine I, Ruhr-University Bochum, Bochum, GermanyEmail timm.westhoff@elisabethgruppe.deBackground: Geriatric rehabilitation programs primarily aim at an increase of mobility and functional autonomy of the elderly. The cardiovascular effects of these programs, however, remain elusive. Since regular physical exercise is associated with numerous beneficial cardiovascular effects including a reduction of blood pressure (BP), the present prospective study investigates the hemodynamic effects of a representative standardized rehabilitation program.Methods: A total of 74 subjects who were hospitalized in a German university hospital for geriatric rehabilitation were enrolled in the study. Peripheral BP, central aortic BP, 24h-ambulatory BP, heart rate and pulse wave velocity as a measure of arterial stiffness were assessed at admission and before discharge from the hospital. The program contained 4– 5 sessions of physical activity of individualized intensity per week (≥ 30 min/session, eg, walking, cycling, stair rising).Results: The mean age of the study population was 82.4± 6.9 years; all patients suffered from arterial hypertension (stage 2– 3) with a median number of three antihypertensive drugs. The most frequent cause for admission was injurious falls. The mean duration of the rehabilitation program was 17 days and comprised at least 20 physical activity sessions including occupational therapy. The program led to a significant improvement of mobility (Timed Up & Go 29.5± 18.5 vs 19.1 ± 9.3 s, p< 0.001) and Barthel index of activities of daily living score (46.6± 19.1 vs 69.8± 16.5, p< 0.001). Peripheral systolic BP decreased from 135.4± 19.0 mmHg at baseline to 129.0± 18.4 mmHg at follow-up (p=0.03), whereas peripheral diastolic BP, central aortic BP, 24h-ambulatory BP, heart rate and pulse wave velocity as a measure of arterial stiffness were not significantly altered (p> 0.05 each).Conclusion: The present representative standardized geriatric rehabilitation program was able to improve mobility, which showed a mild effect on systolic BP but did not affect 24h-ambulatory BP.Keywords: exercise, rehabilitation program, geriatric, blood pressure, hypertension